Extraction Of Tungsten From A Hydrothermal Deposit - A. E. Raddatz (Society for Mining, Metallurgy & Exploration, 1982)
The U.S. Department of the Interior, Bureau of Mines, is investigating methods for recovering tungsten from domestic resources. A calcine-quench-leach (CQL) technique was developed for the extraction of tungsten from the Golconda, Nevada, hot springs ores. The deposit contains disseminated tungsten, which cannot be beneficiated by conventional techniques and must be treated by hydrometallurgical methods. The CQL procedure consists of calcining the ore at 900° C for 3 hr, quenching in a solution containing 1.5 parts of NazCO3 and 1.5 parts of NaOH per part of WO3 in the ore and at a solution- to-ore ratio of 3 to 1, leaching at 200° C and at 250 psig for 3 hr, and filtering and washing the residue. A series of closed-circuit batch tests showed that 92 pct of the tungsten was extracted from a sample containing 2.32 pct WO3. The pregnant solution contained 11 q of W03/1.